(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Cyberbullying is bullying that takes place by using digital technology. This type of bullying may include social media networks, text messages, and emails. Despite being relatively new, cyberbullying is now well-recognized as a serious public health problem affecting children and adolescents. Cyberbullying affects kindergarten to Grade 12 (K-12) students as follows: negative affects mental and physical health, academic performance, school-related well-being, and interpersonal relationships. Mental health is important at every stage of life, from childhood and adolescence through adulthood. Thus, this study aimed to determine the effect of cyberbullying on the mental health of senior high school students of Bestlink College of the Philippines. The study utilized a descriptive method design. The survey research design was chosen to observe in a completely natural and unchanged natural environment without affecting the normal behavior of the respondents. The survey included questions about the profile of the respondents in terms of age, gender, highest educational attainment of parents, and monthly family income. The questionnaire also included questions about how the respondents perceive cyberbullying in terms of impact, extent, and commonly recorded social media applications that are related to cyberbullying. Facebook is the most commonly recorded social media application about cyberbullying with 49 or 98%. The questionnaire also included questions regarding the challenges encountered by victims of cyberbullying in terms of the emotional aspect, physical aspect, mental aspect, spiritual growth, and personal growth. 5. The questionnaire also included questions about the response of students regarding the negative comments on social media sites. The majority of the respondents answered that their friends helped overcome the sadness they felt after reading negative comments on social media. The questionnaire also included a section where the students can write their suggestions to prevent or overcome insults on social media sites. Many respondents suggested that people should think several times before posting on Facebook, Instagram, and Twitter to prevent receiving insults on social media sites. Students should know the causes and effects of cyberbullying. Students must also consider the possible positive and negative comments on their posts. The school administrators should also strengthen the implementation of their rules and regulations on cyberbullying, and teachers should attend seminars and lectures to provide necessary interventions for cyberbullies.